2010
DOI: 10.1007/s11214-010-9652-0
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Magnetic Field Observation and Initial Global Mapping of Lunar Magnetic Anomalies by MAP-LMAG Onboard SELENE (Kaguya)

Abstract: The magnetic field around the Moon has been successfully observed at a nominal altitude of ∼100 km by the lunar magnetometer (LMAG) on the SELENE (Kaguya) spacecraft in a polar orbit since October 29, 2007. The LMAG mission has three main objectives:(1) mapping the magnetic anomaly of the Moon, (2) measuring the electromagnetic and plasma environment around the Moon and (3) estimating the electrical conductivity structure of the Moon. Here we review the instrumentation and calibration of LMAG and report the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 51 publications
5
95
0
Order By: Relevance
“…The lunar magnetometer (LMAG) on Kaguya measured the magnetic field vectors at a sampling rate of 32 Hz (Tsunakawa et al 2010). We performed fast Fourier transformation (FFT) to the magnetic field vectors in every 16 s to analyze wave activities in the frequencies from 0.0625 to 16 Hz.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lunar magnetometer (LMAG) on Kaguya measured the magnetic field vectors at a sampling rate of 32 Hz (Tsunakawa et al 2010). We performed fast Fourier transformation (FFT) to the magnetic field vectors in every 16 s to analyze wave activities in the frequencies from 0.0625 to 16 Hz.…”
Section: Observationsmentioning
confidence: 99%
“…(f) The spacecraft trajectory during 00:00 to 01:00 UT (green line) and magnetic field vectors (magenta arrows) with respect to the Moon. The black contour indicates 0.5-nT magnetic field strength at an altitude of 100 km (Tsunakawa et al 2010). The yellow and gray hemispheres in (f) represent the dayside and nightside of the Moon, respectively.…”
Section: Fundamental and Harmonic Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic field data used in this study were obtained by the lunar Lagnetometer (LMAG) of the magnetic field and plasma experiment (MAP) on board Kaguya (Shimizu et al 2008;Takahashi et al 2009;Tsunakawa et al 2010) on its orbit encircling the moon at an altitude of 100 km during the period from 1 January 2008 to 30 September 2008. The period of the orbital motion was about 118 min at that altitude.…”
Section: Instrumentationmentioning
confidence: 99%
“…The reflected protons injected into the solar *Correspondence: nakagawa@tohtech.ac.jp 1 Tohoku Institute of Technology, 35-1 Yagiyama Kasumi-cho, Taihaku-ku, 982-8577, Sendai, Japan Full list of author information is available at the end of the article wind flow generate a variety of wave activity around the moon. Large amplitude, nearly monochromatic ultra-lowfrequency (ULF) waves of 0.01 Hz (Nakagawa et al 2012;Tsunakawa et al 2010) and non-monochromatic whistler waves within the extremely low-frequency (ELF) range from 0.03 to 10 Hz (Nakagawa et al 2011;Tsugawa et al 2012) were most commonly observed around the moon. Significant monochromatic whistler waves were also seen, although they were less common (Nakagawa et al 2003;Tsugawa et al 2011).…”
Section: Introductionmentioning
confidence: 99%